Factors affecting immune responses to the influenza vaccine - Maria R. Castrucci (Taylor & Francis Group, 2018)
Annual administration of the seasonal influenza vaccine is strongly recommended to reduce the burden of disease, particularly for persons at the highest risk for the viral infection. Even during years when there is a good match between the vaccine and circulating strains, host-related factors such as age, preexisting immunity, genetic polymorphisms, and the presence of chronic underlying conditions may compromise influenza vaccine responsiveness. The application of new methodologies and large-scale profiling technologies are improving the ability to measure vaccine immunogenicity and our understanding of the immune mechanisms by which vaccines induce protective immunity. This review attempts to summarize the general concepts of how host factors can contribute to the heterogeneity of immune responses induced by influenza vaccines.